Analysis of The Urgency of The Need for Regent Regulations on Tourism Awareness Groups (Case Study of Bogor Regency) - Wulandari, Siswi (CV. Publikasi Indonesia, 2024)
To implement community-based tourism, it is necessary to regulate the role of the community in the form of tourism awareness groups to improve the position and role of the community as an important subject or actor in tourism development and can synergize and partner with relevant stakeholders in improving the quality of tourism development in an area. Seeing the great potential possessed by Bogor Regency and the importance of the role of the Tourism Awareness Group as an implementer of conscious tourism, regulations are needed as legal certainty and guidelines for the Regional Government, Tourism Awareness Group, and the Community in the implementation and development of tourism in Bogor Regency. The type of research used is qualitative. The purpose of this study was to identify the role and contribution played by tourism awareness groups (Pokdarwis) in tourism development in Bogor Regency. The research method used in this study is qualitative. The results showed that the Regulation on Tourism Awareness Groups in Bogor Regency specifically does not yet exist. On the other hand, the existence of the Tourism Awareness Group has a major role in supporting a conducive climate for tourism growth, so it is considered necessary to establish a Regent Regulation on Tourism Aware Groups.